Թեոդորոս Մոպսուեստացին իբրև Անտիոքյան դպրոցի նշանավոր աստվածաբան - Հովհաննես Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
Эта статья – попытка проанализировать теологию известного богослова Антиохийской школы - Феодора Мопсуестийского. Влияние его идей и мыслей огромно как на богословские школы его эпохи, так и более позднего времени. Антропологический аспект его богословия сыграл важную роль в развитии богословской мысли. Hovhannes Hovhannisyan in this article attempts to analyze the theology of Theodore of Mopsuestia, the famous theologian of Antioch. The impact of Theodore of Mopsuestia’s theological ideas and thoughts was immense on the theological schools of his time and of all later times. In fact the Christian anthropological aspect of his theology has played an important role in the formation of the theological thought of the Church in general.
Keywords: Christianity; Doctrinal Theology